Taking the Ballgame Out to the World: An Analysis of the World Baseball Classic as a Global Branding Promotional Strategy for Major League Baseball - Benjamin D. Goss (Journal of Applied Sports Management, 2009)
This paper analyzes the 2006 World Baseball Classic as a promotional strategy by Major League Baseball to further its global branding pursuits. The WBC is qualified as a global sport event that is a marketing function of MLB in its efforts to emerge as an international brand; elements of the WBC are examined in the context of a global brand strategy. WBC promotional execution elements are studied in light of dimensions upon which consumers evaluate global brands. Four customer segments targeted through the WBC are characterized before the paper examines future WBC marketing approaches in the context of cultural production.
Keywords: Institutional leadership; NFL; Institutional disruption